Synthesis and Properties of Multistimuli Responsive Shape Memory Polyurethane Bioinspired from α‐Keratin Hair. Issue 7 (14th May 2021) - Wu, Guanzheng; Panahi‐Sarmad, Mahyar; Xiao, Xueliang; Dong, Ke; Mei, Xi; Li, Siming; Li, Ruiqing; Hou, Xiuliang
Abstract: Herein, a multistimuli responsive shape memory polyurethane (multiresponsive SMPU) containing disulfide bonds (–S–S–), bioinspired from α‐keratin hair component, was synthesized using a two‐step reaction and activated via four‐varied stimuli, including water, heat, redox agent, and UV‐light. First, the prepolymer was prepared by the reaction between the comonomers of hexamethylene diisocyanate and polycaprolactone‐2000, and once ended, 1, 4‐butylene glycol and 3‐mercapto‐1, 2‐propanediol (C3 H8 O2 S) have been appended to the prepolymer to initiate the chain‐extension reaction. The chemical structure and properties of the multi‐responsive SMPU were decoded by FT‐IR, XRD, DSC, and Raman spectra. The correlation between microstructure, dynamic‐mechanical‐analysis, and shape‐memory properties of the multi‐responsive SMPU were systemically discussed. As a primary clue, the opening/closing of H‐bonds and disulfide bonds approved that they dictated the shape memory performance. The clear‐cut results clarified that the multiresponsive SMPU endowed composition‐dependent stress relaxation, and its reversible variation of storage modulus was examined by changing temperature. Owing to such molecular switches, the strip pieces were able to represent a multistimuli responsive shape memory effect —induced by water, heat, redox agent (NaHSO3 ‐H2 O2 solutions), and UV‐light. This research paves a feasible road to prepare a novel multistimuli responsive shape memory actuator with high potential features in flexible sensor and robotic applications. Abstract : A multistimuli responsive shape memory polyurethane comprising disulfide bonds, bioinspired from α‐keratin hair component, has been synthesized and activated via four‐varied stimuli, including water, heat, redox agent, and UV‐light. As regards such molecular switches of H‐bonds and disulfide bonds, the strip pieces have represented a desirable multi‐stimuli responsive shape memory effect —induced by all various stimuli.